If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 58 = 3(2 + 5x) Reorder the terms: 58 + 2x = 3(2 + 5x) 58 + 2x = (2 * 3 + 5x * 3) 58 + 2x = (6 + 15x) Solving 58 + 2x = 6 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 58 + 2x + -15x = 6 + 15x + -15x Combine like terms: 2x + -15x = -13x 58 + -13x = 6 + 15x + -15x Combine like terms: 15x + -15x = 0 58 + -13x = 6 + 0 58 + -13x = 6 Add '-58' to each side of the equation. 58 + -58 + -13x = 6 + -58 Combine like terms: 58 + -58 = 0 0 + -13x = 6 + -58 -13x = 6 + -58 Combine like terms: 6 + -58 = -52 -13x = -52 Divide each side by '-13'. x = 4 Simplifying x = 4
| 8x-(4x+7)+11=2x | | 7v^2-2v=0 | | 2a+6-6a= | | -(6m+4)=4m-2(6m+2) | | 9a+3b+c=1750 | | -4k+2(5k-6)= | | 20n^2-16n-160=0 | | -4/.75 | | 81x^2-1/16 | | 5+6y-18y= | | 3y+2y-8=17 | | 4x+8=2(3+x)+2(x+1) | | (6x-10)(4x-9)= | | 2x^2+10x-85=0 | | x-6=9-4x | | 2n^2+25n+63=0 | | 14-(-8x)+4x-(-12)= | | 3(b+4)+b=-6(3+b) | | 7n^2+6n+42=0 | | 7x-(6x+8)=3x-46 | | 11+3x-7=6x-5-3x | | 2w+10=22 | | 2+3(2-5)-8=2(x-5) | | 1.5x-0.5y=12 | | -1=1/3x-6 | | 4x+8=2(5+2x) | | 4x+8=2(5+2x)7 | | 2a-9=5a-12 | | 0=2-5x+y | | 7x-4=6x+7 | | 1.3x+5y=20 | | 2v+5v+3= |